(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Ancient Indian physicians were well aware of the use of plants as anti-implantation, abortifacients, and contraceptives. This article contains up-to-date research on medicinal plants that are anti-fertility. The aim of this analysis is to illustrate plant-based anti-fertility studies. Herbs may offer solutions for women who are reluctant to utilize current means of contraception due to side effects or other factors, and lowering fertility is superior to using other contraceptives. Researchers will be able to use this report to help them classify medicinal plants with anti-fertility properties.